Categories and approaches to pedagogical problematisation - Mariagrazia Contini (Ricerche di Pedagogia e Didattica, 2006)
During the years in which Italian Society was heavily conditioned by the fascist regime and later by the tragedy of the war, Banfi based his perspective and university teaching on two fundamentals: from the theoretical point of view, he proposed a critical and anti-dogmatic theory of reason and from the ethical point of view, he asserted a free and profound humanism.